RENAL DYSFUNCTION PATHOGENETICALLY BASED PHARMACOLOGICAL CORRECTION USING LIPOPROTEIN WITH SORBITOL AND HAES-LX-5 % HYPEROSMOLAR COLLOIDAL SOLUTIONS IN CONDITIONS OF THYROID GLAND BURNING - Tiron, O.I.; Vastyanov, R.S.; Horoshkov, O.V. (World of Medicine and Biology, 2023)
The purpose of the study was to investigate the lipoprotein with sorbitol and HAES-LX 5 % hyperosmolar colloidal solutions impact on kidney functioning peculiarities in the dynamics of thyroid gland burning. The expressed kidney function disorders manifested by their filtrative, excretory and detoxicative functions disturbances occur throughout the 30 days of the postburn process together with lipoperoxidative processes acceleration and antioxidant protection suppression within the kidneys parenchyma. Kidneys functional activity disturbances were proved to reach their maximal expression on the 3rd – 14th days of the study. Lipoprotein with sorbitol and HAES-LX 5 % hyperosmolar colloidal solutions revealed nephroprotective effects in terms of nephrocyte damage free radical mechanism prevention, the antioxidant protection enzymatic link activation and kidney specific functions recovery. Used hyperosmolar colloidal solutions optimal protective activity occurs on the 7th – 14th day of the trial and lasts until the end of the experiment. Thus, the scheme of thyroid gland burning pharmacological correction including the lipoprotein with sorbitol and HAES-LX 5 % hyperosmolar colloidal solutions administration is pathogenetically justified and be able not only to restore the nephrocytes functional activity but also to prevent their damage throughout the post-burn process dynamics.
Keywords: thyroid gland; thermal injury; kidneys; hyperosmolar colloid solutions pathogenetic mechanisms; pathological dysregulation